THE MEDIATING EFFECT OF ATTITUDE ON THE RELATIONSHIPS BETWEEN WHATSAPP USAGE, KNOWLEDGE, AND BEHAVIORAL IMPACT - Md Saydul Haque; Saodah Wok, (INTERNATIONAL JOURNAL OF LAW, GOVERNMENT AND COMMUNICATION (IJLGC), 2024)
With millions of users worldwide, WhatsApp has truly become an outstanding and one of the quickest developing information exchange platforms that the modern world has ever seen. The application offers many useful features to people all around the world. More specifically, its use has remarkably changed how lecturers and students communicate and share information. With this in mind, this study attempts to investigate the effect of WhatsApp usage in a tertiary educational institution in Malaysia. The specific objectives of the study are to determine the level of usage, attitude, knowledge, and behavioral impact of WhatsApp communication; to analyze the relationships between behavioral impact, usage, knowledge, and attitude in using WhatsApp communication; and to test the mediating effect of attitude on the relationships between WhatsApp usage, knowledge, and behavioral impact. The underlying theory used in this study is the media richness theory. The study employed the quantitative research design with the survey method and online questionnaire as the research instrument for data collection. A total of 161 respondents from International Islamic University Malaysia (IIUM) participated in the study. The results revealed a high level of WhatsApp usage, a positive attitude, high knowledge, and a positive behavioral impact of WhatsApp communication among IIUM postgraduate students. Attitude partially mediated the relationships of WhatsApp usage and knowledge with behavioral impact.